Literature Review: Implementasi Pelayanan Farmasi Klinik di Rumah Sakit di Indonesia Berdasarkan Permenkes RI 72/2016 - Bella Shafira; Elin Yulinah Sukandar (LPPM Institut Pendidikan Nusantara Global, 2026)
This study is a literature review that aims to evaluate the implementation of clinical pharmacy services in Indonesian hospitals based on Permenkes RI Number 72 Year 2016. This study reviewed relevant scientific articles published from 2015-2025 obtained from the Google Scholar database with a focus on the implementation of clinical pharmacy services by pharmacists in hospitals. The findings show that the implementation of clinical pharmacy services has a positive impact on the quality of health services, especially in reducing patient mortality and the incidence of preventable adverse drug events. Pharmacists play a central role in therapeutic evaluation, monitoring drug use, education, and collaboration with other health workers. Overall, although clinical pharmacy services play an important role in improving quality of care and patient safety, their implementation in Indonesia has not been optimized as a whole and still requires improved facilities, personnel, and training to support the implementation of all established service standards.